Rheology of mine tailings deposits for dam break analyses - Débora Magalhães Chácara; Waldyr Lopes Oliveira Filho (REM: International Engineering Journal, 2021)
Abstract This article deals with the rheology of tailings deposits related to dam break analysis. The material used was a fine tailings from iron ore processing. Geotechnical and rheological characterization of these tailings were performed. The rheological characterization consisted of rotational and oscillatory tests. It was observed that the rheological properties depend on material solids content and sample preparation method. Furthermore, the material showed viscous or viscoplastic fluid behavior, depending on the solids content. The results of the rheological tests were used as input in numerical flow simulations using Flow-3D® software. Failure of a hypothetical tailings deposit was simulated, with different scenarios. Relationships between traveled distance (range, spreading), speed, and time of arrival of the flow wave versus rheological properties were determined. It was found that tailings runs are also strongly influenced by the solids content and deposit stress history (formation), resulting in different flow types ranging from mudflood, through mudflow, and even landslide. A major finding was that in the Flow-3D® analyses, the deposit volume mobilized, and the output hydrograph are parts of the solution, and not premises or a model to follow (e.g. design breach).